THE REORGANIZATION OF ECONOMIC ACTIVITIES IN THE APUSENI MOUNTAINS - MAGDALENA DR ĂGAN (Revue Roumaine de Géographie)
The reorganization of economic activities in the Apuseni Mountainspresents several aspects of transition from the centralized economy of the communist period to the market economy after 1990, in a miningmountainous area. The present paper shows the rising of other industrial branches and of tourism development following the collapse of the mining and metal-processing industries. At the same time, small-scale individual initiative replaces the centralized decision, while the importance of external investments is still essential.